A case study to estimate the applicability of secondary structures of SSU‐rRNA gene in taxonomy and phylogenetic analyses of ciliates. (26th June 2015) - Wang, Pu; Gao, Feng; Huang, Jie; Strüder‐Kypke, Michaela; Yi, Zhenzhen
<x xml:space="preserve">Abstract</x> Phylogenetic studies of ciliates are mainly based on the primary structure information of the nuclear genes. Some regions of the small subunit ribosomal RNA (SSU‐rRNA) gene have distinctive secondary structures, which have demonstrated value as phylogenetic/taxonomic characters. In the current work, we predict the secondary structures of four variable regions (V2, V4, V7 and V9) in the SSU‐rRNA gene of 45 urostylids. Structure comparisons indicate that the V4 region is the most effective in revealing interspecific relationships, while the V9 region appears suitable at the family level or higher. The V2 region also offers some taxonomic information, but is too conserved to reflect phylogenetic relationships at the family or lower level, at least for urostylids. The V7 region is the least informative. We constructed several phylogenetic trees, based on the primary sequence alignment and based on an improved alignment according to the secondary structures. The results suggest that including secondary structure information in phylogenetic analyses provides additional insights into phylogenetic relationships. Using urostylid ciliates as an example, we show that secondary structure information results in a better understanding of their relationships, for example generic relationships within the family Pseudokeronopsidae.